GPNMB-Positive Cells in Head and Neck Squamous Cell Carcinoma-Their Roles in Cancer Stemness, Therapy Resistance, and Metastasis - Yohei Kawasaki; Hitomi Suzuki; Hitomi Suzuki; Shinsuke Suzuki; Takechiyo Yamada; Maya Suzuki; Ayumi Ito; Haruka Hatakeyama; Masahito Miura; Yasufumi Omori (Frontiers Media S.A., 2022)
Objective: Despite the use of surgical and chemoradiation therapies, head and neck squamous cell carcinoma (HNSCC) still has a poor prognosis. Immune checkpoint inhibitors have been shown to prolong life expectancy but have limited efficacy. Glycoprotein nonmetastatic melanoma protein B (GPNMB) has received significant attention in breast cancer treatment, in which it has been associated with cancer stem cells (CSCs) and epithelial-mesenchymal transition (EMT); however, the function of GPNMB in HNSCC is completely unknown. This study aimed to clarify the characteristics of GPNMB-positive cells in vitro and their association with the prognosis by immunostaining clinical specimens.Methods: We examined the sphere formation, invasion, and migration ability of GPNMB-positive cells in four HNSCC cell lines in vitro. We also immunostained biopsy specimens with GPNMB from 174 patients with HNSCC diagnosed, treated, and followed-up in our institution to evaluate overall survival and progression-free survival.Results: GPNMB-positive cells showed enhanced sphere formation, invasion, and migration, suggesting that they could have CSC characteristics and the ability to induce EMT, as reported for breast cancer. Clinical specimens showed that overall survival was 39.4% and 57.8% (p = 0.045) and that progression-free survival was 27.6% and 51.6% (p = 0.013) for the high-expression and the low-expression groups, respectively, indicating poor prognosis for the high GPNMB group. The high GPNMB group was also more resistant to chemoradiation and bioradiotherapy. GPNMB was more highly expressed in metastatic lymph nodes than in the primary tumor.Conclusion: GPNMB-positive cells might have CSC characteristics and induce EMT. Detailed functional analyses of GPNMB in HNSCC and the establishment of therapies targeting GPNMB will lead to improved prognoses.